Estrategias didácticas y su influencia en el desarrollo de la motricidad gruesa en los niños de 8vo de la Unidad Educativa Francisco Huerta Rendón - Piza Ramirez, Noely Magdalena (2025)
This research work aims to determine the didactic strategies implemented by physical education teachers to promote the development of gross motor skills in 8th grade students, as well as to evaluate the level of development of these skills through standardized tests and analyze the relationship between the strategies used and motor development. The methodology used included a quantitative approach, with the application of standardized tests to measure the motor skills of the students. Surveys were carried out with teachers to identify the didactic strategies applied in physical education classes. The main findings reveal that a high percentage of students have deficiencies in gross motor skills, which highlights the need to improve teaching methodologies. In addition, a significant correlation was identified between the quality of the didactic strategies and the level of development motor, This suggests that continuous teacher training and the implementation of structured programs can have a positive impact on gross motor development. Keywords: gross motor skills, didactic strategies, physical education, development